2020
DOI: 10.1109/access.2020.3028863
|View full text |Cite
|
Sign up to set email alerts
|

Marine Dissolved Oxygen Prediction With Tree Tuned Deep Neural Network

Abstract: Changes in the dissolved oxygen concentration of the ocean have important implications for marine ecosystems and global climate change. However, limited by measurement techniques, the hydrology data is not always complete. Thus, accurate prediction on marine dissolved oxygen concentration (MDOC), is a powerful supplement to the current observation data. Deep neural network is a powerful model to do the prediction, while it is usually difficult and time-consuming to tune its structure. Meanwhile, deep jointly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, the combination of different ML algorithms has its advantages, a combination of tree-based models and neural networks termed a Marine-Deep Jointly Informed Neural Network (M-DJINN) estimates the DO in the ocean. 14 The M-DJINN method uses a zero-mean Gaussian distribution to predict the marine DO concentration. By choosing the number of trees and the maximum depth of trees, the M-DJINN proved to be more efficient than DJINN in terms of computing time and prediction ability.…”
Section: Chemical Oceanographymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the combination of different ML algorithms has its advantages, a combination of tree-based models and neural networks termed a Marine-Deep Jointly Informed Neural Network (M-DJINN) estimates the DO in the ocean. 14 The M-DJINN method uses a zero-mean Gaussian distribution to predict the marine DO concentration. By choosing the number of trees and the maximum depth of trees, the M-DJINN proved to be more efficient than DJINN in terms of computing time and prediction ability.…”
Section: Chemical Oceanographymentioning
confidence: 99%
“…ML has shown to have better performance in the prediction of DO. However, the combination of different ML algorithms has its advantages, a combination of tree-based models and neural networks termed a Marine-Deep Jointly Informed Neural Network (M-DJINN) estimates the DO in the ocean . The M-DJINN method uses a zero-mean Gaussian distribution to predict the marine DO concentration.…”
Section: Chemical Oceanographymentioning
confidence: 99%
“…The rectified linear unit (ReLU) was used as the activation function and the Adam optimizer was used to minimize the cost function. While a number of methods have been used to tune NN hyperparmeters [15,16], DJINN has been proven to accurately construct a NN without an extensive optimization search in a number of different settings [17,18]. To ensure the DJINN models used were optimized, the number of trees and the maximum depth of the decision trees were varied and tested on the validation setup.…”
Section: Applying Djinn To Transport Problemsmentioning
confidence: 99%
“…L. Wang et al used the PSO–SELM–PLS prediction model, and the experimental results showed that the three metrics RMSE, MAPE, and MAE were 0.270, 0.0371, and 0.2284, respectively. L. Wang et al [ 13 ] and J. Liu et al [ 14 ] proposed M-DJINN and wavelet transform-depth Bi–S-SRU prediction models, respectively, and the proposed models achieved 96% prediction accuracy. A. Bilali et al [ 15 ] developed stochastic gradient descent for linear regression (SGD), an artificial neural network (ANN), k-nearest neighbors (k-NN), and support vector machine (SVM) prediction models for chloride concentration and the sodium adsorption ratio using physical parameters as inputs to the models, and SGD and ANN outperformed the other methods in terms of R 2 and RMSE.…”
Section: Introductionmentioning
confidence: 99%